Analisis Bibliometrik Stunting Spasial Menggunakan VOSviewer - Marisa Meliana Fitri; Iswandi U; Nurhasan Syah; Elsa Yuniarti (Jurnal Penelitian Pendidikan IPA, 2023)
Stunting, or stunted growth, is a serious global public health problem. The aim of this research is to investigate the dynamics of co-occurrence, trends and saturation of keywords in spatial studies related to stunting using the literature review method. This research uses bibliometric analysis with the help of Web Lens.org, Openrefine, and VOSviewer for data collection and analysis. VOSviewer can display bibliometric mapping in three different visualizations, including network visualization, overlay visualization, and density visualization. The findings of this research reveal seven topic clusters related to the subject of this research, with network visualization results showing that research with the keywords 'spatial' and 'stunting' is still relatively limited. The overlay visualization results show that this research trend only emerged at the beginning of 2020 and has not yet reached saturation point. In conclusion, there is still a lot of room for further research in this area, making spatial stunting an interesting and potentially useful area for further exploration.